Letter from the Democratic State Central Committee of Califonia - WM. A. Munnell:::::: (1960)
A letter to Jane Tolmach that discusses that the Democratic State Finance committee voted to send money to all Democratic Congressional, State Senatorial and Assembly incumbents.